Hubungan Kepercayaan Diri Dengan Intensitas Pemakaian Alat Listrik Pada Mata Kuliah Perawatan Kulit Wajah Dengan Teknologi - Farah Fatmasari Munandar; Eti Herawati; Neneng Siti Silfi Ambarwati (Mathematics Education Study Program, 2025)
This research was conducted to determine the relationship between self-confidence and the intensity of using electrical devices in facial skin care courses with technology. This study uses a survey method with a quantitative approach. The study population was students of the Jakarta State University cosmetology education study program class of 2022 as many as 44 students, the sample technique used was Total Sampling. The data collection technique used a questionnaire to measure self-confidence and intensity of using electrical devices in facial skin care courses with technology. The results showed that there was a positive relationship between self-confidence and the intensity of using electrical devices in facial skin care courses with technology, with a correlation coefficient value of 0.595 (> 0.297) and a significance value of 0.01 (< 0.05). The majority of students have self-confidence with moderate categories in the interval 32-48 with a percentage of 80% and the majority of students have the intensity of using electrical devices with moderate categories in the interval 24-36 with a percentage of 64%. In conclusion, self-confidence has an important role in increasing the intensity of using electrical appliances. The higher the self-confidence of students, the higher the intensity of using electrical appliances. In further research it is recommended to explore how much influence students' self-confidence has on the intensity of using electrical devices in facial skin care courses with technology.